Getting India back on track : an action agenda for reform - Debroy, Bibek; Tellis, Ashley J. (Carnegie Endowment for International Peace, 2014)
India has fallen far and fast from the runaway growth rates it enjoyed in the first decade of the twenty-first century. In order to reverse this trend, New Delhi must seriously reflect on its policy choices across a wide range of issue areas. Getting India Back on Track broadly coincides with the 2014 Indian elections to spur a public debate about the program that the next government should pursue in order to return the country to a path of high growth. It convenes some of India's most accomplished analysts to recommend policies in every major sector of the Indian economy. Taken together, these seventeen focused and concise memoranda offer policymakers and the general public alike a clear blueprint for India's future. Contents Foreword Ratan N. Tata (Chairman, Tata Trusts) Introduction Ashley J. Tellis and Reece Trevor (Carnegie Endowment for International Peace) 1. Maintaining Macroeconomic Stability Ila Patnaik (National Institute of Public Finance and Policy) 2. Dismantling the Welfare State Surjit Bhalla (Oxus Investments) 3. Revamping Agriculture and the Public Distribution System Ashok Gulati (Commission for Agriculture Costs and Prices) 4. Revisiting Manufacturing Policy Rajiv Kumar (Centre for Policy Research) 5. Generating Employment Omkar Goswami (Corporate and Economic Research Group) 6. Expanding Education and Skills Laveesh Bhandari (Indicus Analytics) 7. Confronting Health Challenges A.K. Shiva Kumar (National Advisory Council) 8. Accelerating Infrastructure Modernization Rajiv Lall and Ritu Anand (IDFC Limited) 9. Managing Urbanization Somik Lall and Tara Vishwanath (World Bank) 10. Renovating Land Management Barun S. Mitra (Liberty Institute) and Madhumita D. Mitra (consultant) 11. Addressing Water Management Tushaar Shah (International Water Management Institute) and Shilp Verma (independent researcher) 12. Reforming Energy Policy and Pricing Sunjoy Joshi (Observer Research Foundation) 13. Managing the Environment Ligia Noronha (Energy and Resources Institute) 14. Strengthening Rule of Law Devesh Kapur (University of Pennsylvania) and Milan Vaishnav (Carnegie Endowment for International Peace) 15. Correcting the Administrative Deficit Bibek Debroy (Centre for Policy Research) 16. Building Advanced Technology Capacity for Competitive Arms Acquisition Ravinder Pal Singh (Stockholm International Peace Research Institute) 17. Rejuvenating Foreign Policy C. Raja Mohan (Observer Research Foundation and Carnegie Endowment for International Peace.